2002
DOI: 10.3349/ymj.2002.43.1.7
|View full text |Cite
|
Sign up to set email alerts
|

Detection ofHelicobacter pyloriAntigen in Stool by Enzyme Immunoassay

Abstract: Invasive techniques for diagnosis of Helicobacter pylori (H. pylori) infection require an endoscopic examination which is expensive and inconvenient and may cause complications. Stool cultures for H. pylori or a direct detection of H. pylori antigen in stools by PCR are expensive, tedious, and have a low sensitivity. We recently used an enzyme immunoassay (EIA) to detect H. pylori antigen in stool specimens. A total of 41 patients were seen at Inha University Hospital, Inchon, Korea between September and Octob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 0 publications
1
14
0
1
Order By: Relevance
“…In Arabidopsis, cell separation during floral organ abscission after pollination and lateral organ emergence are regulated by the peptide INFLORESCENCE DEFICIENT IN ABSCISSION, which signals through the Leu-rich repeat receptor-like kinases HAESA and HAESA-LIKE2, and the process is involved in the regulation of cell wall remodeling (Stenvik et al, 2008;Kumpf et al, 2013). Increasing evidence implicates the involvement of PUB-ARM proteins in various plant receptor-like kinase signaling pathways, and the ARM domains mediate binding to the kinase domains (Gu et al, 1998;Kim et al, 2003;Samuel et al, 2006Samuel et al, , 2008Mbengue et al, 2010;Lu et al, 2011). For example, the PUB-ARM proteins PUB12 and PUB13 attenuate the activity of the Arabidopsis flagellin-sensing receptor 2 by ubiquitination and subsequent degradation (Lu et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In Arabidopsis, cell separation during floral organ abscission after pollination and lateral organ emergence are regulated by the peptide INFLORESCENCE DEFICIENT IN ABSCISSION, which signals through the Leu-rich repeat receptor-like kinases HAESA and HAESA-LIKE2, and the process is involved in the regulation of cell wall remodeling (Stenvik et al, 2008;Kumpf et al, 2013). Increasing evidence implicates the involvement of PUB-ARM proteins in various plant receptor-like kinase signaling pathways, and the ARM domains mediate binding to the kinase domains (Gu et al, 1998;Kim et al, 2003;Samuel et al, 2006Samuel et al, , 2008Mbengue et al, 2010;Lu et al, 2011). For example, the PUB-ARM proteins PUB12 and PUB13 attenuate the activity of the Arabidopsis flagellin-sensing receptor 2 by ubiquitination and subsequent degradation (Lu et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In their patient group 6 of 63 (9.5%) patients were H. pylori positive. On the other hand, in another patient group where 31 of 41 (75.6%) patients were H. pylori positive, 87.1% sensitivity and 100% specificity were detected according to the manufacturer's cut-off value, and 100% sensitivity and 90% specificity were detected according to the calculated cut-off value of 0.024 by ROC curve analysis (Kim et al 2002). These two studies may indicate that in low H. pylori prevalent populations the cut-off values of HpSA test are higher whereas in high H. pylori prevalent populations the cut-off values are lower which is in accordance with our results.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the sensitivity of the HpSA test was found and specificity. In these studies, the best cut-off values calculated by ROC curve analysis were from OD; 0.024 to 0.3 (Ohkura et al 2000;Leodolter et al 2001;Kim et al 2002;Kato et al 2003;Syam et al 2005). In our dyspeptic patients, the best cut-off value calculated by ROC curve analysis was 0.048 and by using this cut-off value, the sensitivity of the test increased from 51.1% to 92% without decreasing the specificity of the test.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Microbial epoxide hydrolases can be produced in large amounts by using recombinant DNA technology [50,51]. Most of synthetic applications of epoxide hydrolases have been achieved by using bacterial enzymes or fungal enzymes [52,53].…”
Section: Epoxide Hydrolase-catalyzed Enantioselective Hydrolysismentioning
confidence: 99%